Recent Multicast Routing Protocols in VANET: Classification and Comparison (Journal of University of Babylon for Engineering Sciences, 2018)
Vehicular Ad Hoc Network (VANET) classified as one of the most important classes of next generation networks that developed in recent years rapidly for vehicles and road transmissions. It can help in implementing a large set of applications related to vehicles, traffic light, traffic jam, drivers, passengers, ambulance, police, fire trucks and even pedestrians. Routing is the most prominent problem in the transmission of information in VANETs and there are many modes of dissemination: unicast, broadcast, multicast and geocast. In this paper, we will focus only on the multicast that is referring to a process of sending information from one node (called source vehicle) to a group of nodes that found in different locations (called destination vehicles). The purpose of this paper is to study the existing multicast routing protocols in VANET and produce good survey about them and determine the advantages and disadvantages of each one as well as classify them into different categories based on some effected parameters such as quality of service, vehicle trajectory and etc. After analyzing these routing protocols we concluded that there is persistent need to produce efficient multicast routing protocol in this network to decrease the resource consumption and improve the overall performance.